Development of an in vitro regeneration system for Heinsia crinita (Afz.) G. Taylor via direct induction of shoot proliferation from explants - Peter Nkachukwu Chukwurah; Aniefiok Ndubuisi Osuagwu; Oluwasegun Olamide Fawibe; Ekerette Emmanuel Ekerette (BMC Research Notes)
Abstract Objective The African bush apple (Heinsia crinita) is a highly valued orphan shrub that supports the nutritional and natural medicine needs of many sub-Saharan African communities. However, the crop remains poorly conserved and without any known genetic improvement. Accordingly, the current study sought to develop for the first time, an in vitro regeneration system based on direct shoot proliferation from its stem and hypocotyledonary explants using combinations of two cytokinins (benzyl adenine – BA, thidiazuron – TDZ) and the auxin (naphthalene acetic acid (NAA), in Murashige and Skoog (MS) medium. Results Combinations of BA and NAA effectively induced multiple shoot formation from stem and hypocotyledonary explants of the crop. The most effective treatment (1.0 mg/L BA + 0.1 mg/L NAA) induced an average of 13.77 and 30.32 shoots per responsive hypocotyl and stem explants, respectively. Combinations of TDZ and NAA were less effective in promoting shoot induction in the explants at the concentrations tested compared to BA and NAA combinations. Hypocotyledonary explants achieved complete plant regeneration without multiple shoot formation in a hormone-free MS medium. In vitro shoots regenerated from both stem and hypocotyledonary explants were 100% successfully rooted on a half-strength hormone-free medium, and acclimatized to produce H. crinita plants with over 90.0% efficiency.